The study of man : an introduction - Linton, Ralph (New York D. Appleton-Century Co., 1936)
Contents: human origins; race; the significance of racial diffirences; the background of human mentality; the background of culture; the distinctive aspects of culture; society; status and role; the raw materials for society; the family...
Keywords: Cơ bản